When is it worth being a self‐compatible hermaphrodite? Context‐dependent effects of self‐pollination on female advantage in gynodioecious Silene nutans. Issue 9 (11th April 2015) - Lahiani, Emna; Touzet, Pascal; Billard, Emmanuelle; Dufay, Mathilde
<x xml:space="preserve">Abstract</x> This study investigates empirically how self‐pollination interplays with male sterilty, which are two major traits of plant reproductive systems. Such interactions have been considered by several theoretical studies but never fully verified empirically. In particular, we directly show that being self‐compatible provides hermaphrodites with a reproductive assurance. Our study thus allows a better understanding of reproductive strategies in flowering plants.